Lived experiences of Zimbabwean labour migrants in the informal economy in Urban Cape Town during the COVID-19 pandemic - Chinhara, Betty (Department of Social Development, 2024)
This research investigated the lived experiences of Zimbabwean labour migrants in the informal economy in urban Cape Town during the COVID-19 pandemic (hereafter referred to as COVID-19). The study was undertaken in Cape Town, South Africa. The major issues investigated included the lived experiences of Zimbabwean labour migrants in informal economy during COVID-19. The coping mechanisms used by Zimbabwean migrants to survive during the pandemic and the role local institutions played in enhancing the adaptation of migrants to the challenges that came with the COVID-19 was investigated. This qualitative study recruited 20 participants from Zimbabwe using purposive and snowball sampling. Face- to-face and telephonic interviews were used in data collection. The data was then analysed using thematic data analysis. Two theoretical frameworks; social exclusion theory and capability approach, were used in understanding designing of the study, and understanding the findings. The findings uncovered various challenges that were faced by Zimbabwean migrants during COVID-19. These include loss of livelihood opportunities, failure to send remittances home, unexpected changes in their social life, and exclusion from state-provided COVID-19 response packages. The findings further showed that to cope or adapt to these constraints Zimbabwean migrants adopted various mechanisms. These mechanisms included spending money from their pre-pandemic savings, relying on their social networks (family and friends) and some local institutions (churches and non-governmental organisations) for food, and financial support. The study discovered that COVID-19 helped some Zimbabweans to learn new skills to create entrepreneurial opportunities for themselves. A combination of these coping strategies demonstrated a high level of migrants' resilience which is critical in reducing their vulnerability relative to the effects of future pandemics and ongoing exclusions. The study concluded with recommendations. These included that the policy makers to be more inclusive of vulnerable migrants in formulating policies. There is need to provide social protection to migrants in difficult times such as the pandemic.